Investigating Mathematical Knowledge of Teaching for Secondary Preservice Teachers in Papua New Guinea - Olowa, Murray (Southeast Asian Mathematics Education Journal, 2023)
This article examines the studies investigating the teacher’s mathematics knowledge  of teaching  by  secondary  preservice teachers  in Papua  New  Guinea. Previous  research  on Mathematics  Knowledge  for  Teaching  provided  support  for  the  study.  This  study  was conducted  in  recognition  of  the  ongoing  problems  with Papua  New  Guinea's  curriculum, particularly the  teaching  of  science  and  mathematics,  which  have  led  to  a  drop  in  students' performance  in  these  subjects.  Subject  Matter  Knowledge  (SMK)  and  Pedagogical  Content Knowledge  (PCK)  are  the  two  main  domains  that  have  been  identified.  These  domains  are further  subdivided  into  Knowledge  of  Content  and  Students  (KCS),  Knowledge  of  Content and Teaching (KCT), and Knowledge of Content and Curriculum (KCC), respectively. Other subdivided   areas   include   Common   Content   Knowledge   (CCK),   Specialized   Content Knowledge  (SCK),  and  Horizon  Content  Knowledge  (HCK).  To determine  the  relationship between  SMK  and  PCK,  research  questionnaires  were  utilized  as  instruments  that  could accommodate  the  various  areas  of  SMK  and  PCK. Given  that  the  P-value  is  0.22>0.05,  the study's  findings  indicate  a  marginally  significant  difference  in  SMK  between  years  one  and four.  However,  since  the  P-value  was  0.007<0.05,  it  was  discovered  that  year  fours  have higher  PCK  than  year  one.  Ultimately,  the  study  has  demonstrated  that  fourth  years  have higher   MKT   than   first   years.   The   diligent   work   of   final-yearpreservice   teachers   in mathematics  is  what  caused  this  difference.  It  is  advised  that  the  mathematics  curricula  in teacher  colleges  be  reviewed  following the  findings  and  expanded  to  include  material  on SMK  and  PCK. The  Secondary  Teachers  College  Program  Specification  Document  must include both what and how to teach mathematics.